Isolation and expression analysis of anther-specific gene BcACT from Brassica campestris ssp. chinensis, syn. B. rapa ssp. chinensis - JIANG Ming; CAO Jia-shu (浙江大学学报. 农业与生命科学版, 2009)
According to known sequences of actin genes published in GenBank, full length primer pairs were designed. The gene, designated BcACT, was successfully isolated from both mixed flower buds cDNA and leaf genomic DNA of Brassica campestris ssp. chinensis (L.) Makino. RT-PCR methods were used to analyze gene expression patterns within different organs of three materials and flower bud parts of maintainer line. The results showed that BcACT was 1704 bp in length with 3 introns, and the complete coding sequence (CDS) of BcACT was 1134 bp in length encoding 377 amino acids. RT-PCR results showed that BcACT was expressed in flower buds of both maintainer Bcajh97-01B and Polima CMS line Bcpol97-05A. However, there was no detection in Ogura CMS line Bcogu97-06A. Further studies showed that BcACT gene was an anther-specific one and up-regulated expression during anther development.